(untitled) (TERRA LATINOAMERICANA, 2019)
Agriculture (including livestock) is considered one of the main sources of greenhouse gases. Monitoring greenhouse gases (GHG) is necessary in this activity, and there are several methodologies. One of these methodologies is the eddie covariance technique, which can analyze GHG in a continuous manner. Accordingly, the installation and evaluation of a GHG-2 system was proposed for monitoring CH4 and CO2 in a dairy herd in a semi-confined system in Sonora. The results show that the GHG-2 can evaluate the continuous behavior of the CH4 and CO2 emissions, observing peaks of both gases when the cattle were present. It also corroborated the existence of a good relationship between both GHG (CH4:CO2), similar to previous studies, where this ratio was used to estimate methane emissions indirectly through energy balances to calculate CO2. One of the limitations of this technique in confined or semi-confined systems is the presence of particulate matter in the atmosphere that requires frequent monitoring and maintenance of the equipment, as well as the high consumption of energy, which forces us to consider solar panels and batteries to supply an adequate flow of electricity if another continuous source of electricity is not available.